The Effect of Shopping Lifestyle and Sales Promotion on Impulse Buying Moderated By Openness To Experience on Shopee - Riska Anastasia Ningrum; Afrima Widanti (International Journal of Management and Digital Business, 2023)
This research aims to analyze the effect of shopping lifestyle and sales promotion on impulse buying with openness to experience as a moderating variable in shopee e-commerce users. This research method was quantitative, and online questionnaires collected primary data. Participants of this research as counted 200 individuals who used as sample. This research used PLS-SEM with the help of the SmartPls version 3.3.9 to analyze the data. This research showed that testing the first hypothesis indicates that the higher the shopping lifestyle, the more impulse buying in online shopping will increase. Second, the results of the two hypotheses indicate that the research hypothesis is accepted. It means the higher the sales promotion, the higher the level of impulse buying that occurs in online shopping. Finally, the third test results show that the research hypothesis is accepted and that openness to experience could impact sales promotions on impulse buying. Three factors influence impulse buying, shopping lifestyle, sales promotion, and openness to experience.